纸上开国 ——书籍媒介、知识制作与《皇明英烈传》中的国朝意识: The Birth of the Glorious Ming ——Books, Knowledge Production and the Formation of Dynastic Consciousness in The Record of Heroes and Martyrs - Liu, Chiung-yun Evelyn (ERUDITE: Journal of Chinese Studies and Education, 2020)
由书籍形式与知识制作的角度切入，本文以广泛流行于晚明，陈建（1497-1567）编写的国朝通史《皇明通纪》，以及作者不详讲述明代开国事迹的《皇明英烈传》为中心，重新思考中国文学史上历史演义的生成变化及其文化意涵，并进一步分析《英烈传》这类书籍如何透过图文合作、符号运用、排版方式等设计，整理、简化知识讯息以协助阅读，如此同时满足读者“认识”我朝历史“知”的欲望以及对于英雄崛起、布衣发迹故事的喜好，于“再制”知识以利书籍行销传播的过程中，形成某种“国朝意识”。 Abstract By examining the intertwined relationship between Chen Jian’s (1497-1567) Huang Ming tongji 皇明通紀 (Comprehensive Annals of Imperial Ming) and the anonymous historical novel Yinglie zhuan 英烈傳 (The Record of Heroes and Martyrs), this paper demonstrates that these two works together play a significant role in disseminating knowledge about the founding of the Ming dynasty from mid-sixteenth century onward. It first inspects how these two works and their later editions borrow from each other. Then, by paying special attention to the book forms of The Record of Heroes and Martyrs, including the charts, illustrations, and special marks that serve as reading aids for the reader, this paper analyzes how these special designs might have helped the reader grasp historical information and envision the past of the dynasty in a way hard to achieve before the proliferation of books. While previous studies tend to downplay these historical novels for their Confucian didacticism and lack of artistic sophistication, this paper argues that it may be more fruitful to understand these books as cultural products that respond to the reader’s desire to “know,” to possess knowledge of “our” history, which in turn create a sense of participate in a community of shared information and dynastic consciousness. Keywords: Huang Ming tongji, Yinglie zhuan, book history, yanyi, tongjian, Ming Qing, historical novel